The Theory of Status in Ancient Rhetoric - Vardumyan, Atom (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
The   significant   role   of   philosophy   in   the   development   of   spiritual culture of humanity is manifested not only in more than substantial volume of knowledge, but also in its methodology of formation and evaluation of knowledge   at   large.   As   much   as   our   mind   is   fundamentally   inclined   to objectivity   and   accuracy,   life,   especially   human   realities,   have   been   and remain to be subject to various interpretations, and, equivalent, but at the same time contradicting ideas. And its “culprit” is not the shortcoming or inconsistency of our thought, but the inexhaustibility of possible descriptions of any phenomenon in combination with the universal realities of the world. This fact makes it difficult – if not impossible – the universal de9nition and assessment  of  phenomena,  events  and  developments  of  human  life.  The separation of truth and error, good and evil, useful and harmful, fair and unfair, acceptable and unacceptable, good and bad is still on the agenda of intense philosophical debates and a problem in the practice of organizing social life and social processes.With the mission of coordination and interpretation of such problems, rhetoric   was   brought   to   life   in   ancient   culture   as   practical   methodology enabling   to   achieve   common   conclusion   and   persuasion   through argumentation,   and   an   opportunity   to   propose   philosophically   grounded solutions to universal issues. Among them, the theories on statuses and loci are   especially   topical.   Today,   they   are   well   elaborated   theories   that   are widely used in judicial and political processes, live speeches, discussions and debates.   Moreover,   in   our   perspective   introduction   of   jury   courts   and   in today’s reality of democratization of the political 9eld, it seems more than important to discuss rhetoric in general and the theories presented in the present   article   in   particular,   especially   for   those   who   are   active   in   the mentioned spheres of activity.
Keywords: rhetoric; types of rhetoric; controversial issue; speech strategy; statuses; loci; extralogical argument; defnition and assessment; rejection